PERANCANGAN PROTOTIPE APLIKASI PEMILIHAN BIBIT CABAI RAWIT HIBRIDA VARIETAS UNGGUL - Onny Marleen; Suharni Suharni; Anggraeni Ridwan; Rani Puspita (Universitas Muhammadiyah Semarang, 2018)
Seedlings are one of the most important components in growing cayenne pepper. In general, farmers grow cayenne pepper seeds from the seeds they obtained at the time, even though there are many varieties of cayenne pepper seeds available in the community. To choose the desired chili seeds is not an easy thing to do because the variety varies. The purpose of this study was to help farmers in choosing superior varieties of hybrid cayenne pepper seeds according to the criteria desired by farmers. AHP method is one method that can help farmers choose the variety of cayenne pepper seeds. In this study, the AHP method was used to select cayenne pepper seeds, with 14 alternative varieties of hybrid cayenne pepper seeds along with 10 criteria. The criteria include age at harvest, old fruit color, fruit shape, yield, fruit size, number of fruit per tree, weight per fruit, fruit taste, fruit retention and fruit skin surface. To make it easier for farmers to choose superior varieties of chili seeds, the prototype application was designed. The results of this study are prototype applications designed to help farmers to choose superior varieties of hybrid cayenne pepper. Keywords: chili seeds, AHP, prototypes